Choice of treatment based on Turkish hypertension consensus report: Do we follow the recommendations? - Gülden Yürüyen; İlkim Deniz Toprak; Zeki Toprak; Murat Akarsu; Pınar Demir; Yücel Arman; Eylem Özgün Çil; Mustafa Özcan; Sedat Irmak; Özgür Altun; Şengül Aydın Yoldemir; Hasan Eruzun; et al. (KARE Publishing, 2018)
Objective: The aim of this study was to determine how often the recommendations of the Turkish Hypertension Consensus Report are followed, and to draw attention to the report. Methods: The demographic information of 1000 patients diagnosed with hypertension and the details of the antihypertensive medications prescribed at the outpatient service of a tertiary care hospital were recorded, and the data were compared with the recommendations of the report. Results: The mean age of the patients was 62+-11 years. In all, 623 (62.3%) of the 1000 patients were women, and 377 (37.7%) were men. A combination of an angiotensin II receptor blocker (ARB) and a diuretic was the most frequently observed prescription. A diuretic was the most used antihypertensive drug (58.7%), followed by an ARB (48.8%). However, as a monotherapy, a calcium channel blocker (CCB) was the most commonly used antihypertensive drug (19.2%). The most frequently used antihypertensive drug group in older patients was diuretics (63.6%), as proposed in the report. Beta blockers (49.1%) were used more often than expected. For the diabetic group also, a diuretic (60.7%) was the most frequently used antihypertensive drug, followed by an ARB (51.1%) and a CCB (45.2%). Angiotensin-converting enzyme (ACE) inhibitors (34.6%) were the fifth most preferred antihypertensive drug class. However, when ACE inhibitors and ARBs were considered as a single group, known as renin-angiotensin system (RAS) blockers, these RAS blockers were the most prescribed antihypertensive drug class, followed by diuretics. In the group of patients with coronary artery disease, treatment was found to be generally consistent with the report, but the use of diuretics was greater than expected. Lastly, 124 of 160 patients who had chronic kidney disease were given RAS blocker therapy, which was in line with the consensus report recommendations. Conclusion: Antihypertensive therapies were individualized, as suggested by the consensus report. However, there are proposals still to be considered in special patient groups.